Advances in cardiovascular supplementation: mechanisms, efficacy, and clinical perspectives - Wu, Xun; Fang, Tanwei (Frontiers in Molecular Biosciences, 2026)
The integration of nutritional supplementation into cardiovascular disease (CVD) prevention and management represents a dynamic and often contentious field. Moving beyond traditional paradigms, recent research has sought to elucidate the precise molecular mechanisms, establish robust clinical efficacy through large-scale trials, and identify specific patient populations that may derive the greatest benefit. This review synthesizes the current evidence on key supplements—including omega-3 fatty acids, coenzyme Q10 (CoQ10), magnesium, and selenium—evaluating their roles from biochemical, translational, and clinical viewpoints. We explore the conditions under which certain supplements have transitioned from general wellness products to targeted therapeutic adjuvants, address the controversies surrounding their use, and discuss future directions for research and clinical application.